Fabrication of Ceramic Alumina Tube by Extrusion Method - Suzanne Agustin; Kristanto Wahyudi; Rizky Berliana Wijayanti; Maulid Purnawan (Balai Besar Keramik, 2019)
Ceramic tubes are widely used as process equipment in various industries. One of the materials used as raw material for ceramic tubes is alumina. Materials are processed by vacuum extruder to obtain products with constant cross section. The characteristics of the products depend on the amount and chemical composition of the crystals formed. The formation of mullite as the main mineral will increase thermal shock resistance because mullite has a low expansion coefficient. Composition B with the percentage of 50% alumina, 30% kaolin, 10% clay and 10% MgO provide the best temperature shock resistance. The measurement result for flexural strength of composition B is 2400.52 kg / cm2